Investigating Teacher’s Implementation of the Gendre-Based Approach in Teaching Writing a Vocational School - Istianah, Lailatul; Nugraheni, Dyah Ayu; Tjendani, Endah Nur (UIBU, 2026)
This study looks at how the Genre-Based Approach's used to teach English writing at a vocational high school. The Genre-Based Approach is not often studied in this type of school. The researchers used a method to study two English teachers. They collected data by observing classes and doing interviews. The results show that one teacher was better at creating a fun and collaborative classroom while the other teacher was more structured in using the Genre-Based Approach. Both teachers had problems, such as students not knowing many words being unmotivated not having enough time and not having enough resources. The study found that the Genre-Based Approach is not about following steps but also about how well teachers adapt to the classroom and students needs. This study helps us understand how the Genre-Based Approach is used in schools, where students need to learn practical skills.